The Influence Of Leadership, Work Morale, And Work Environment On Employee Work Discipline At The Department Of Cooperatives, Industry, And Trade In Medan City - Esha Syahputri; Wilchan Robain; Abdi Setiawan (Universitas Dehasen Bengkulu, 2026)
The research analysis aims to analyze leadership, work spirit and work environment on work discipline. The data analysis technique used is the associative research method with the help of the SPSS version 23 program. This study uses multiple linear regression analysis. The sample in this study was 69 respondents. Primary data collection used a questionnaire. The results of the study indicate that leadership has a positive and significant effect on employee work discipline at the Cooperatives, Small and Medium Enterprises, Industry and Trade Office of Medan City seen from the results of data processing with a t-value of 3.999> t-table of 1.99 with a significant value of 0.000 <0.05, then the hypothesis H1 is accepted and H0 is rejected. Work morale has a positive and significant effect on employee work discipline at the Medan City Cooperatives, Small and Medium Enterprises, Industry, and Trade Office, as seen from the data processing results. The calculated t-value is 2.607 > t-table of 1.99 with a significance value of 0.000 < 0.05. Therefore, hypothesis H2 is accepted and H0 is rejected. The work environment does not significantly influence employee work discipline at the Medan City Cooperatives, Small and Medium Enterprises, Industry, and Trade Office, as seen from the data processing results. The calculated t-value is 1.391 < t-table of 1.99 with a significance value of 0.000 > 0.05. Leadership, work morale, and the work environment simultaneously significantly influence employee work discipline at the Medan City Cooperatives, Small and Medium Enterprises, Industry, and Trade Office, as seen from the calculated F-value of 13.368, which is greater than 2.74 and a significance value of 0.000 less than 0.05.